Mother's Experience of Banjar Tribe for Handling Fever in Children Under Five Years Old in Banjarmasin City - Esme Anggeriyane (East Asian Journal of Multidisciplinary Research, 2022)
Most parents have different perspectives when handling fever such as providing medical or traditional complementary therapy. However, therapy based on culture is more believed by parents to be a treatment for children with fever due to supernatural disorders. The research aimed was to explore mother's experience for handling fever in children under five years old in Banjarmasin city. This study employed a qualitative study with a transcendent phenomenology design. The data collection was carried out by in-depth interviews with five mothers who had children under five years old in Banjarmasin City. The theme of the research is the mother's actions in handling children with fever. This research can be used as developing a standard operating procedure for handling children with fever according to evidence-based nursing in the development of complementary therapy.